The poison of love - Meera K R (Hamish Hamilton, an imprint of Penguin Random House India, 2017)
When Tulsi first meets Madhav, she is irrevocably drawn to his chiselled good looks and charm. Although wary of his many dalliances and the string of broken hearts left in his wake, she is surprised by the intense desire that Madhav arouses in her. And before long, she forsakes her family, her prospective career, her fiancé--all for the love of this inscrutable man. But love can be like poison. And nothing can prepare Tulsi for the heartache and betrayal that lie ahead. Years later, Tulsi escapes to the ancient city of Vrindavan, seeking redemption amidst the cries and prayers of its anguished widows. However, when her past catches up with her, old wounds resurface with dramatic consequences